Assessing child satisfaction and expectations for developing a child-friendly environment at the pediatric department in a general hospital in Qatar - Pattabi, Amudha; Nazarene, Ananth; Varghese, Sejo; Hassan, Samiya Mohamud; Nashwan, Abdulqadir J.; Patil, Surekha Kiran; Singh, Kalpana (Frontiers in Pediatrics, 2024)
'Patient-centred' care positions the patient at the core and emphasises fulfilling their unique needs, preferences, and values. This approach is particularly significant in the context of children. Although widely recognised as necessary, this approach is not universally implemented. The children find themselves in hospital wards, where they are required to follow protocols and systems designed primarily for adults. In the appropriate atmosphere, children often express themselves more effectively through words, body language, and play, leading to a richer understanding of their needs. There is growing recognition of the importance of addressing children's concerns regarding hospital environments. This study investigates children's satisfaction with physical environment of the hospital. Insights from this exploration could provide valuable input for creating hospital environments centred around children's needs and preferences. This mixed-methods study involves children aged between 6 and 14 years with parental consent. The survey used nine items to gauge satisfaction with the existing hospital environment as a 'child-friendly hospital' and another nine items to explore their expectations for such environments. The Mann-Whitney U and Kruskal-Wallis tests as well as thematic analysis were employed to assess the statistical significance of differences in satisfaction levels and children's expectations of the hospital's physical environment. A total of 398 children participated in the study. Of these, 40.3% were aged 6 to 8 years; 60.3% had experienced two to five hospital visits; 55.8% of children participated during their outpatient service visit; and 31.7% were Asian. Children's satisfaction levels with various aspects of the hospital environment-including its physical appearance, signage, lounge, consultant rooms, corridors, bedrooms, TV content, toys, and staff uniforms ranged from 42.9% to 59%. The children expressed a desire for a hospital environment that is spacious, colourful, attractive, and filled with cartoon characters and toys in the children's hospital from the front lounge to the inpatient units.The findings underline the importance of considering the perspectives of children in evidence-based healthcare design. The study reveals that children's satisfaction with the hospital environment is generally average or below average. Ultimately, a 'child-friendly hospital environment' integrates children's rights into healthcare to significantly improve outcomes.